Morningness-eveningness in adolescents - Díaz-morales, Juan Francisco; Gutiérrez Sorroche, María (The Spanish Journal of Psychology, 2008)
Individual morningness-eveningness differences explain the rhythmic variations of behavioral and biological patterns. Several studies have corroborated that morningness preference increases over adulthood and aging. Adolescents shift their time of day preferences from morningness to eveningness during puberty. The aims of this study were translate to Spanish the Morningness-Eveningness Scale for Children (MESC) and to analyze age and sex differences. A group of 600 adolescents (aged between 12 and 16 years) participated in the study. Psychometric analysis showed that reliability and factor structure were suitable and similar to previous studies. The results indicated a clear decrease of morningness as of 12 years. Boys were more morningness-oriented than girls in several items of the questionnaire. In view of the results, several educational implications are raised.